2006
DOI: 10.1111/j.1582-4934.2006.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes in immune regulation

Abstract: Exosomes are small vesicles originating from late endosomes, 30–100 nm in diameter with typical cup-shape morphology. They are reported to bear high levels of a narrow spectrum of molecules involved in immune response and signal transduction. Apart from removing obsolete membrane proteins, some surprising biological functions of exosomes were unveiled recently and their applications in immunotherapy of tumors are currently intensively investigated. Dendritic cell- (DC) and tumor-derived exosomes have considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 88 publications
(120 reference statements)
1
113
0
Order By: Relevance
“…15,[21][22][23] Their precursors are intracellular vesicles packaged into MVB, which fuse with the plasma membrane, releasing exosomal vesicles into the extracellular milieu. 15,[21][22][23] Exosome-like nanovesicles are somewhat smaller (20-50 nm), of irregular shape and probably stem also from endosomal compartments. 15 Apoptotic blebs are bigger (50-500 nm), of heterogenous shapes and result from budding of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23] Their precursors are intracellular vesicles packaged into MVB, which fuse with the plasma membrane, releasing exosomal vesicles into the extracellular milieu. 15,[21][22][23] Exosome-like nanovesicles are somewhat smaller (20-50 nm), of irregular shape and probably stem also from endosomal compartments. 15 Apoptotic blebs are bigger (50-500 nm), of heterogenous shapes and result from budding of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes produced from mature dendritic cells express high levels of both MHCI and MHCII, as well as costimulatory and adhesion ligands. In contrast, exosomes from immature DCs show a different protein profile including NFGE8 (a phagocytosis-inducing factor), FasL, and TRAIL (an apoptosis-inducing ligand) (Li et al, 2006). Recent data suggest that exosomes from tumor cells often express immunosuppressive ligands, such as NKG2D, whose expression allows the evasion of tumor cells from T cell and NK cell killing (Clayton et al, 2008).…”
Section: Molecular Composition Of Exosomesmentioning
confidence: 99%
“…While that result can be interpreted that DCs provide T cells with the bystander costimulatory ligands and cytokines necessary to promote T cell activation, it is also possible that cognate peptides in exosomes are transferred to MHCs intrinsically expressed by DCs after uptake. Indeed, one study has shown that CD4 + T cells are activated only when both exosomes and DCs express MHCII and fail to be activated when DCs lacking MHCII are used (Li et al, 2006).…”
Section: Physiological (Immunological) Roles Of Exosomesmentioning
confidence: 99%
“…When released from leukocytes that have internalized and processed microbial or other foreign proteins, exosomes will contain MHCII loaded with antigenic peptide (pMHCII exosomes) [115]. A growing literature indicates that these released pMHCII exosomes can activate remote T lymphocytes either by direct antigen presentation from the pMHCII displayed on the exosome surface, or an indirect pathway wherein the pMHCII exosomes are taken up by remote naive dendritic cells for DC-mediated antigen presentation [116][117][118]. In addition to this model of "remote" antigen presentation, released exosomes may be used for other novel types of intercellular communication including the cell-to-cell transfer of: (1) intact mRNAs and microRNAs [119]; and (2) the direct transfer of oncogenic growth factor receptors from tumor cells to remote non-transformed cells [120].…”
Section: P2x7r-induced Release Of Multivesicular Body (Mvb)-derived Ementioning
confidence: 99%